Supportive Communication Skills as a Protective Factor Among Couples Experiencing Incarceration - Durante, Katherine A. (Criminal justice and behavior, 2023)
We employ an ABC-X model of family stress theory lens to examine the association between several communication skills and patterns and relationship quality within heterosexual couples where the man is incarcerated and the woman is not. Using data from the Multi-site Family Study on Incarceration, Parenting and Partnering and multinomial logistic regression, we found that couples who are regularly able to work out their differences have a lower relative risk of drifting apart in their relationship. Couples who frequently have heated arguments have both increased relative risks of becoming closer together and drifting apart. Multivariate linear regression analyses revealed that more frequently having a sense of humor and being able to work out differences is associated with increased relationship happiness while having more frequent heated arguments and a partner who interrupts is associated with decreased relationship happiness during incarceration. Prison programs should include training on improving couples’ communication skills.